Analisis Kinerja Instansi Pemerintah Daerah Dengan Pendekatan Balanced Scorecard - Dwi Rahmanda, Ardian Rido; Suyanto, Suyanto; Darmayanti, Elmira Febri (Universitas Muhammadiyah Metro, 2022)
This study aims to measure the performance of the Metro City Health Office, Lampung using the Balanced Scorecard approach. Performance measurement is carried out based on four perspectives of the Balanced Scorecard, namely financial perspective, customer perspective, internal business process perspective, and growth and learning perspective. This type of research is quantitative qualitative research (mix methods) using case studies at the Metro City Health Office, Lampung. Sources of data used are primary and secondary data sources. Collecting data using the method of documentation, questionnaires, and interviews. Respondents came from community service users and employees of the Metro City Health Service, Lampung. The sampling technique used was purposive sampling and convenience sampling. The financial perspective is measured using a value for money approach. The results of this study indicate that the performance of the Metro City Health Office, Lampung seen from the perspective of customers, finance, internal business processes, and growth and learning, overall has good performance quality.